Penerapan Porter Five Forces dan Analisis SWOT dalam Perencanaan Strategi PT Sweet on Stevia - Muh Anwar Rasyid; Febriandana Akbar; Ilham Fahrirrijal; Eka Bayu Bachtiar Ferdiansa; Agung Nugroho (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Indonesia, as the world's sixth largest sugar market, faces an imbalance between sugar consumption and production, opening up opportunities for natural sweetener alternatives such as stevia. Stevia, which is low in calories and has the potential to reduce the risk of chronic diseases, is increasingly in demand. However, optimal business strategies to market stevia in Indonesia are still limited. This article aims to analyze PT Sweet on Stevia's business strategy by using Porter Five Forces and SWOT analysis. The method used is to link the two analyses to determine strategies in the aspects of service, marketing and sales, and operations. The results of the analysis show the importance of improving service quality, social media-based marketing, and operational efficiency in facing market competition. The findings provide insights for PT Sweet on Stevia to optimize its business strategy and contribute to the promotion of healthier sugar consumption patterns in Indonesia.